Tool vs. Kreativitas Mengukur Peran Software Penulisan Naskah dalam Proses Kreatifdan Efisiensi Penulis - Dr. RR. Ella Evrita Hestiandari, S.E, M.M, Dr. RR. Ella Evrita Hestiandari, S.E, M.M (Akademi Komunikasi SAE Indonesia, 2024)
Writing screenplays for movies has changed significantly in the digital age due to technological advancements.. This study explores the impact of the use of scriptwriting software such as Final Draft, Celtx, and Scrivener on the creative process and efficiency of writers. The software offers features that make it easier for writers to follow classic narrative structures, increase productivity, and manage manuscripts more effectively. Through interdisciplinary analysis, this study examineshow integrating classical screenwriting theory, such as Aristotle's three-act structure, with modern software can affect the quality and efficiency of writing. The results show that while software like Final Draft and Celtx can improve efficiency and provide robust structural guidance, there is a risk that reliance on templates can limit writers' creativity. Therefore, it is important for writers to balance the use of technology with creative exploration to ensure that the quality and authenticityof the work is maintained. This research provides insight into the benefits and challenges faced by modern screenwriters in the use of technology, as well as its implications for the quality and originality of their work.